On Freud's theory of law and religion. (September 2016) - Novak, David
Abstract: This paper is a critical engagement with Freud's anthropological theory of the origins of law and religion, which Freud developed as his representation and development of the Oedipal myth. Freud's mythology, it is argued, is the theoretical result of the essentially narrative nature of psychoanalytical praxis. Freud's myth, especially its treatment of patricide as the original sin, is seen to be a displacement of the biblical myth of fratricide as the original sin. It is argued that the biblical myth is more coherent than Freud's myth, and that it corresponds to the reality of the human condition better than Freud's myth. The paper concludes with the suggestion that the acceptance of the biblical myth in place of Freud's does not necessarily entail a rejection of psychoanalysis as a praxis.